Plasmaferesis pada Krisis Myasthenia : Kasus Serial - Suryani, Shila; Adiyanto, Bowo (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
Adrenal gland surgery needs a multidisciplinary team including endocrinologist, radiologist, anesthesiologist, and surgeon. The indications for adrenal gland surgery include hormonal secreting and non-hormonal secreting tumors. Adrenal hormonal secreting tumors present to the anesthesiologist unique challenges requiring good preoperative evaluation, perioperative hemodynamic control, corrections of all electrolytes and metabolic abnormalities, a detailed and careful anesthetic strategy, overall knowledge about the specific diseases, control and maintaining of postoperative adrenal function, and finally a good collaboration with other involved colleagues.